Comparison of GnRh Agonist Microdose Flare Up and GnRh Antagonist/Letrozole in Treatment of Poor Responder Patients in Intra Cytoplaspic Sperm Injection: Randomized Clinical Trial - Nabati, Azar (Glob J Health Sci, 2016)
BACKGROUNDS: the prevalence of infertility is up to 10 to 15 % which 9 to 24 % of them are Poor Ovarian Responders (POR). This study was designed to compare two methods of GnRH Agonist Microdose Flareup (MF) and GnRH Antagonist/Letrozole (AL) in treatment of these patients. METHODS AND MATERIALS: this randomized clinical trial study consisted of 123 patients. In the first step of treatment in both methods FSH, LH, estradiol, anderostandion, testestron in third day of menstruation period and the thickness of endometrium by Transvaginal sonography were evaluated. At the time of HCG injection the thickness of endometrium and follicles which were more than 14mm ware established and hormones were evaluated. Two weeks later serum βhCG and after 6 to 8 weeks Transvaginal sonography were applied to prove the pregnancy. RESULTS: there were 61 patients with mean age of 38.7±4.58 in MF group and 62 patients with mean age of 38.5±4.6 in AL group (P=0.80). At the time of hCG injection there were significant increase in the level of LH, estradiol, thickness of endometrium and follicles more than 14mm in MF patients (P<0.0001). The mean time of ovary stimulation in MF group was 10.72±1.5 and in AL was 8.45±1.2 (P<0.0001). The mean level of gonadotropin which were used was 80.6±20.1 in MF patients and 64.7±16.4 in AL group (P<0.0001). 18 % of MF group and 38.7% in AL group had no normal cycle of ovulation (OR: 2.87, 95% CI: 1.25-6.57, P=0.011). The mean numbers of oocyte and normal fetus in MF was 5.83±3.5 and 3.7±2.5 and in AL was 3±1.69 and 1.4±1.33 (P<0.0001). The number of chemical pregnancy in MF group was 10 (16.4%) and in AL was 3 (4.8%) (OR 3.85, 95% CI: 1.06-14.77, P=0.037). Clinical pregnancy in 10 patients (16.4%) of MF group and 3 (4.8%)in AL was reported. OR 3.85, 95% CI: 1.06-14.77, P=0.037). CONCLUSION: this study showed that MF method of pregnancy leads to more positive results in pregnancy based on chemical and clinical evaluation in comparison with AL and is advised for poor responder patients.